Comparison of perceived and objectively measured sleep quality among elite rowing athletes - Ayar, S.; Karacabey, K.; Aksu, A.; Ayar, A. (International Journal of Applied Exercise Physiology, 2019)
There suggested to be a reciprocal relationship between sleep and exercise capacity, as physical activity is considered to be beneficial for improved sleep quality especially in those with sleep problems while adequate sleep increases exercise capacity and reduces risk of exercise-induced injuries. But the exact mechanism of this relationship and whether being engaged with every kind of sport branch is beneficial to sleep quality is not clear yet. Yet, the demands and expectations from modern people including elite athletes have placed increasing demands by cutting back on sleep despite scientific research is revealing that sufficient sleep is critical for safety, performance and productivity and the cost of insufficient sleep is well beyond than most people recognize. The aim of this study was to investigate profiles of sleep quality in rowing athletes. For this purpose, profiles of sleep quality, both objectively and subjectively assessed in 30 elite male rowing athletes (mean age 19.36±4.1 years) and age (22.20±2.5 years) and gender-matched non-athlete sedentary control individuals. Subjective sleep quality was evaluated using the the Pittsburgh Sleep Quality Index (PSQI); while a metabolic holter (SenseWear armband) was used for obtaining objective sleep quality related parameters. Independent t-test was used for comparing sleep quality between the group means. Statistical significance was set at p<0.05. In elite rower athletes, the means of sleep duration (according to metabolic holter: 442±56 min; according to PSQI: 449±37, p>0.05) and sleep efficiency [(in athletes 85.5±5.0%; in sedentary group 75.9±8.5 % (n=30)] (P<0.05) was better than sedantery individuals. The findings of the present study indicate that both objective and subjective sleep quality of elite rowers was significantly better than non-athlete sedentary controls.